As experiências teatrais mediadas pelo livro didático de arte - Frenda, Perla (2023)
This research believes in the principle, defended by art-education authors and regulatory documents, that the Arts curricular component is one of experiential nature, therefore unable to do without experience. Studying the Arts implies in knowing and experiencing the specifics of their languages, aesthetical manifestations, and connections. Since 2015, via the National Program for Textbooks and Didactic Materials (Programa Nacional do Livro e do Material Didático), the Brazilian government distributes exclusive Art textbooks to public schools. Consequently, it is relevant that textbooks abide by such principle, in which learning is framed by experience. The distress that motivates this study comes from the researcher’s professional practice as an educator and Art textbook author, specialized in Theater. This research analyzes the use of the textbook collection Janelas da arte (BOZZANO; FRENDA; GUSMÃO, 2018a) and aims to investigate if and how the theater propositions within the collection Janelas da arte convert into experiences for middle school students. Considering textbooks educational instruments of dialogue between teachers and students, specific objectives were designed to: (1) analyze if and how teachers use the theater propositions given by the collection; (2) understand how students receive and perform such propositions; and (3) make suggestions, if proposed, for later re-elaboration of the collection, confronting the information produced, the textbooks theoretical and methodological framework, and this research theoretical framework, which is organized as such: art-education (BARBOSA, 2003, 2019; BOAL, 2012, 2015; KOUDELA, 2013; SPOLIN, 2003, 2004, 2010, 2015); the concept of experience (DEWEY, 2010; LAHAYE, LESSARD; TARDIF, 1991; LESSARD; TARDIF, 2009; LOIOLA; THERRIEN, 2001, 2003); and studies on textbooks (BITTENCOURT, 2004; CHOPPIN, 2004; LAJOLO, 1996; MUNAKATA, 2012a, 2012b). This predominantly qualitative research (ANDRÉ, 2007, 2012; TRIVINOS, 1987) produced information through class observations in public schools in the city of São Paulo; interviews with teachers in Bahia; and questionnaires applied to teachers both in São Paulo and Bahia. All participants were currently using the collection Janelas da arte. Information analysis was inspired by Content Analysis (BARDIN, 2016; FRANCO, 2021). Research findings suggest that teachers understand that textbooks give more theoretical support than practical, given that practical development of “theatrical language grammar” – such as theater games – is recurrently subtracted to prioritize dramatic text contexts that could be turned into thematic presentations. However, considering the theatrical propositions observed, students interacted and manifested dedication and interest. Participant teachers had insufficient training and experimental experience to teach theater, and sometimes even Arts, manifested by the lack of knowledge about the theatrical process development and the reproduction of outdated conceptions about the teaching of Arts and theater. As a result, we analyzed that the theatrical practices within the collection Janelas da arte, when performed, promote a meaningful experience process and could be improved by including: suggestions of adaptations to local contexts; more information about giving instructions and guidelines and the use of spaces; ready-to-use propositions; and short plays